Инклузивната култура во редовните училишта - Димитрова Радојичиќ, Даниела; Чичевска Јованова, Наташа (Faculty of Philosophy, Skopje, 2009)
Inclusive education is a rational concept which means wholeness and long transformation of institutional systems in society, especial in education. There are a number of important and unresolved issues relating to inclusive education in theory and practice. With this article we like to consider the important of continued development of inclusive cultures in mainstream schools. There are many arguments that inclusive culture is most inﬂuential aspect of inclusion. If the culture and the climate are not inclusion-friendly then the outcome, irrespective of polices or indeed practices, may not be successful. Results from analyse of attitude of educational staff and parents, and analyse of low, implicated a need of more attend on this aspects, in further. Inclusive cultures, police and practices are important aspects for successful inclusion of students with special needs in regular school.
Inclusive cultures in mainstream schools
Keywords: Inclusion, Inclusive culture